Pengaruh Rasio Profitabilitas, Rasio Likuiditas Dan Rasio Leverage Terhadap Mandatory Disclosure Yang Di Moderatori Firm Size (Studi Perusahaan BUMN 2010–2020) - Cindy Pricylia; Yeni Ariesa; Felia Chen; Mochammad Fahlevi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purposei/aim of thisi studyi isi toi examinei whether thei ratio of Profitabilityi, Liquidityi and Leveragei Affect Mandatory Disclosure which is Moderated by Firm Size in the BUMN sector in 2010-2020. The research usesi deductiveiapproachi method, quantitativei type and descriptivei. Thei amount ofi BUMN enterprise sectori registered on the IDXiare 19 companiesi andi thei samplei thati fulfill the criteriai according to purposivei samplingi is 13 companiesi. This typei of researchi data usesi secondaryi datai. Thei datai used in the pooling data. Thei datai analysisi techniquei ofi thisiresearchi usesi the EVIEWS program. The conclusion from thei resultsi ofi thisi studyi shows thei profitabilityi andiliquidity ratio havei significanti negative effecti oni mandatory disclosure whilei the leveragei ratio andi firmi sizei haveiai positivei effecti oni mandatory disclosurei. Simultaneouslyi profitabilityi ratiosi, liquidityi ratiosi, leveragei ratiosi and firm sizei havei no effecti oni mandatory disclosure. It is proven by f count is 0.8923 and sig value is 0.2617 higher than 0.05. Keywords: Profitabilityi Ratios, Liquidityi Ratios, Leveragei Ratios, Firm Size and Mandatory Disclosure.